Impacto de los medios digitales en la comunicación efectiva post pandemia en la Cooperativa Nueva Buena Fe en el cantón Buena Fe, año 2020 - Carriel Barberan, Hayleen Julissa (2021)
The present project was carried out in the Nueva Buena Fe Cooperative in the Buena Fe canton, in 2020; Its purpose is to publicize the impact of digital media on effective post-pandemic communication, which is very important to have knowledge about the types, uses and importance of digital media in order to be well informed of what happens in the Cooperative and without exposing oneself to the disease, in addition to maintaining effective and continuous communication with family members whether they live near or in different locations in the country or the world. The importance of this project is considered within the area of social communication because it was determined through the application of surveys and this gave the result of the situations that were discovered and on that the conclusions and recommendations were made. It was possible to determine the digital means used in effective post-pandemic communication in the Nueva Buena Fe Cooperative in the Buena Fe canton in 2020, it is WhatsApp, followed by Facebook, Zoom, Instagram and YouTube. The effect of digital media on effective post-pandemic communication was determined, being a positive effect because residents can stay informed and communicated about what is happening around them without exposing themselves to contracting the disease. And information was provided about the impact of digital media on effective post-pandemic communication in the Nueva Buena Fe Cooperative in the Buena Fe canton in 2020 in order to develop future research.